TINJAUAN HUKUM KEKERASAN DALAM ‎RUMAH TANGGA MENURUT HUKUM ‎ISLAM DAN HUKUM POSITIF - Nasution, Beby Ayu (Jurnal Ushuluddin, 2021)
Married couples face various domestic issues, from minor to significant problems. Islamic and positive laws emphasize domestic violence as a critical concern in marriages. This study explores how aggressive behavior at home is evaluated under Islamic and positive legal frameworks using a normative juridical qualitative approach, analyzing legal literature from libraries. Conclusions drawn from discussions indicate that Domestic Violence under Islamic Law is considered unjust and prohibited by Allah, reflecting principles of compassion (rahmatan lil’alamin). Positive Law defines such violence as crimes against humanity, involving discrimination and human rights violations that must be eradicated. Indonesia's Law Number 23 of 2004 stipulates that actions causing physical, sexual, psychological, or other forms of suffering within households, particularly against women, are illegal. Coercion, threats, or deprivation of liberty are explicitly condemned. In summary, both Islamic and positive legal viewpoints strongly oppose domestic violence, stressing the need for substantial societal and governmental measures to establish a safe and fair environment for everyone.